2005
DOI: 10.1159/000089652
|View full text |Cite
|
Sign up to set email alerts
|

Regional Citrate Anticoagulation during Hemodialysis

Abstract: Background: Regional citrate anticoagulation during hemodialysis is promising, but its clinical implementation is routinely cumbersome because a continuous adjustment of calcium infusion at the dialyzer outlet is needed. Duocart biofiltration (DCB) is a new hemodialysis method using a calcium and magnesium-free dialysate containing only sodium chloride and bicarbonate combined with the infusion into the venous line of a solution containing the ionic complement (K, Ca, Mg) and glucose. Since the dialysate is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In regional citrate anticoagulation (RCA) , citrate chelates calcium and blocks the coagulation cascade by lowering the ionized calcium level in ECC, which can be further reduced by using a calcium‐free dialysate . RCA is cumbersome and time consuming, given that monitoring of ionized calcium is mandatory to avoid hypo‐ and hypercalcemia.…”
Section: Resultsmentioning
confidence: 99%
“…In regional citrate anticoagulation (RCA) , citrate chelates calcium and blocks the coagulation cascade by lowering the ionized calcium level in ECC, which can be further reduced by using a calcium‐free dialysate . RCA is cumbersome and time consuming, given that monitoring of ionized calcium is mandatory to avoid hypo‐ and hypercalcemia.…”
Section: Resultsmentioning
confidence: 99%
“…RCA offers considerable advantages compared to heparin, especially prolonged filter lifetime [1,2,3,4,5,6], reduced complement activation [7,8], oxidative stress [9], and granulocyte [8,9,10,11] and leucocyte [12 ]activation. Additionally, RCA may be used if heparin is contraindicated, as in patients with heparin-induced thrombocytopenia [13] or with a high risk of bleeding [14,15,16,17,18,19]. Furthermore, there has been one non-blinded single-centre randomized controlled trial that found reduced mortality in critically ill patients with acute renal failure and RCA compared to low-molecular-weight heparin [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, we applied this feedback to heparin-free DCB sessions. 2 Citrate was injected at a rate of 0.34 mmol per 100 mL blood flow into the arterial line as suggested by Janssen et al 3 Thirty sessions were performed in ten patients, with the calcium reinjection rate automatically adjusted to ID in order to achieve a calcium balance equivalent to that obtained with dialysate calcium at 1.75 mmol/L. We observed a dramatic decrease in ionized calcium and a doubling of whole blood-activated clotting time prior to calcium reinjection, reflecting effective regional anticoagulation.…”
Section: Adjustment Of Calcium Infusion Rate According To Ionic Dialy...mentioning
confidence: 99%
“…In 2005, we applied this feedback to heparin‐free DCB sessions 2 . Citrate was injected at a rate of 0.34 mmol per 100 mL blood flow into the arterial line as suggested by Janssen et al 3 .…”
Section: Adjustment Of Calcium Infusion Rate According To Ionic Dialy...mentioning
confidence: 99%